Rekonstruksi Sanksi Tindak Pidana Anak pada Tahap Penyidikan: Analisis Integratif Hukum Positif dan Hukum Islam di Polres Bungo, Jambi - Ardi Ardi; Abdul Halim; Risnita Risnita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study uses an integrated analysis of positive law and Islamic law at Polres Bungo to investigate the reconstruction of sanctions for juvenile offenders during the investigation stage. Empirical trends suggest a procedural and administrative orientation that may restrict substantive rehabilitation, even though Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak (Juvenile Criminal Justice System Act) formally adopts restorative justice, diversion, and the best interests of the child as guiding principles. Using a multidisciplinary approach that integrates statutory, theological-normative (shar‘i), and historical considerations, this study uses a normative qualitative design based on library research. The theoretical framework incorporates maqāṣid al-sharīʿah as a normative evaluation instrument, legal effectiveness theory, and punishment theories. The findings reveal a conceptual convergence between Indonesian positive law and Islamic criminal jurisprudence in differentiating criminal responsibility based on maturity and prioritizing rehabilitation over retribution. There are still differences, nevertheless, when it comes to age criteria and the classification of sanctions: Islamic law places more emphasis on moral and biological maturity (baligh and tamyīz), whereas positive law focuses on strict legislative boundaries. The predominance of formal legality over psychosocial assessment at the investigative level runs the risk of undermining rehabilitative goals. In order to maintain proportionality and child protection, this study suggests a reconstructive paradigm that operationalizes maqāṣid-based principles, combines thorough psychological evaluation, and improves diversion measures. In addition to realistically advancing the creation of a more equitable, rehabilitative, and child-centered investigative framework, the research theoretically advances the conversation about harmonizing state and Islamic law.